Numerical validation of double punch test for the assessment of tensile strength in natural fiber reinforced concrete. Issue 3 (1st February 2019) - Anania, Laura; D'agata, Giuseppe
ABSTRACT: In this paper, the results of Finite Element Analysis on concrete specimens reinforced by plant fiber and undergone to double punch tests are presented. In finite element analysis, the constitutive law of the material was calibrated by referring to tensile strength obtained by the Chen formulation and fractural energy derived by the double punch test. The analysis was carried out accounting different volume content of natural fibers derived from a very common plant of Sicily (Agave), to ensure the repeatability of the test. Then, the failure load can be determined by finite element analysis and compared with the experimental one. A good accordance between numerical and experimental data permits us to support the use of the double punch test as a more attractive testing method for the evaluation of the mechanical proprieties of the materials. Double punch test, in fact, is much simpler to perform than the split cylinder test method.